EP-336 Compliance of Fluid Balance Charts in Surgical Patients According to NICE Guidelines. (9th August 2022) - Morsy, Hesham; Li, Michael; Davidson, Chris; Gu, Kat; Patel, Dharti; Hollingshead, James; Ali, Maryam
Abstract: Aim: Assess compliance of presence & completion of fluid balance charts for fluid replacement in accordance with NICE Guidelines in the acute surgical admissions population Method: Total of 158 patients were included. We collected data prospectively for surgical patients admitted between 25/02/21–18/03/21 (first cycle) & 12/09/2021–4/10/2021 (2nd cycle). Maximum of 5 patients daily randomly selected via Google random number generator. Data collected in Wards after clerking Data analysed on Day 1 of admission. Surgical Proforma was used to identify if fluid balance chart was requested. Fluid Balance charts used to assess presence & completion of charts Admissions by audit authors were excluded to prevent selection bias. Intervention: Posters in Emergency Assessment Unit and Wards, Teaching to junior doctors, Regular reminder messages to on-call teams. Results: Presence and completion of fluid balance chart in acute surgical admissions in compliance with NICE guidelines for IV Fluid replacement rose from 48% to 64% between cycle 1 and 2, respectively. However, presence and completion of the chart rises significantly from 64% to 100% when it is requested, compared to 58% to 87% in cycle 1. Conclusions: Most patients had a fluid balance chart made available by the nurses still, regardless of having it requested in their surgical proforma. However, we need to request fluid balance charts for all surgical admissions in order to have all of them present and completed properly as most of them will require replacement. This needs to be clearly documented in the surgical proforma on clerking.